Engaging an infrastructure of time production with international law. Issue 3 (16th February 2022) - Gordon, Geoff
Abstract: This article explores international legal entanglements with the infrastructure of Coordinated Universal Time (UTC), a socio-technical construction that comprises the globally definitive measure of seconds, minutes and hours working in lockstep around the world. UTC is produced and maintained with international law, through international administration with social, political, material and technical dimensions. In analysing mutual entanglements of international law with infrastructural relations organized around UTC, the article assesses their imbrication in globalized governance routines and distributive patterns, instantiated here with reference to the field of finance. The article further considers ways to engage legal-infrastructural relations for material change in patterns of governance.